2012
DOI: 10.1111/j.2042-7174.2012.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge and awareness of cardiovascular disease and its risk factors: a cross-sectional study of 1000 Jordanians

Abstract: The present study reports that the general public in Jordan has limited knowledge and awareness of CVD. In planning to positively impact CVD prevention and management, community pharmacists must develop and promote effective and accessible services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
70
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(123 citation statements)
references
References 24 publications
(39 reference statements)
40
70
13
Order By: Relevance
“…The findings of our study showed that paying attention to eat healthy diet is a predictive factor of knowledge and awareness on CVDs. There are consistency in the literature regarding this association [19,23]. Although the difference in culture and food between the two countries North Ireland [23] and Jordan [19], the consistency with our findings imply that people's life style in terms of diet is affected by their health knowledge and perceptions.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The findings of our study showed that paying attention to eat healthy diet is a predictive factor of knowledge and awareness on CVDs. There are consistency in the literature regarding this association [19,23]. Although the difference in culture and food between the two countries North Ireland [23] and Jordan [19], the consistency with our findings imply that people's life style in terms of diet is affected by their health knowledge and perceptions.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, studies in Pakistan and Jordan asserted this association [19,22]. The findings of our study showed that paying attention to eat healthy diet is a predictive factor of knowledge and awareness on CVDs.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Sample size was based on previous studies on the same population [14,15]. Demographic data and categorical variables were summarized using frequency tables.…”
Section: Discussionmentioning
confidence: 99%
“…The significant role of integrating education in a rehabilitation programme has been widely acknowledged by all health professionals. Education is the process of acquiring knowledge and skills that can lead to changes in human behavior, necessary for the maintenance or improvement of health [14] . Given the fact that hospital stay is minimizing, neither health professionals nor patients have adequate time to devote to their education, consequently, education should start immediately after the diagnosis of the disease.…”
Section: Introductionmentioning
confidence: 99%